ANALISIS TINGKAT KEPEDULIAN LINGKUNGAN SISWA KELAS V SD 2 MUHAMMADIYAH KARANGPAWITAN - Rahmasari; Nabella Alani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental awareness is an attitude, behavior, and action shown by individuals in maintaining the environment, avoiding actions that may damage it, and taking responsibility for repairing environmental damage that has occurred. This attitude needs to be instilled in students from an early age, particularly during elementary school, as this period is crucial for shaping students’ character and habits in the future. This study aims to describe the level of environmental awareness among fifth-grade students at SD 2 Muhammadiyah Karangpawitan in the 2025/2026 academic year. This research employed a survey method, with data collected using a non-test technique in the form of a questionnaire. The sample consisted of 41 respondents. The results of the study show that 3 students (7,3%) were in the very high category, 7 students (17,1%) in the high category, 18 students (43,9%) in the moderate category, 11 students (26,8%) in the low category, and 2 students (4,9%) in the very low category. Based on the analysis, it can be concluded that the level of environmental awareness among fifth-grade students at SD 2 Muhammadiyah Karangpawitan falls into the moderate category. These findings indicate that although several students demonstrate a high level of environmental awareness, there is still room for improvement, particularly among students whose environmental awareness is not yet optimal. Therefore, it is recommended that the school further develop and strengthen existing programs related to fostering environmental care as a sustainable character value among students.